Implementation of Family Medicine in Central and Eastern Europe: Experience and Lessons for Ukraine - Yevhen Sobol, Yevhen Sobol; Myroniuk, Roman; Harust, Yurii; Myrhorod-Karpova, Valeriia (Journal of History Culture and Art Research, 2020)
The reform of the healthcare system in Ukraine is a prime necessity, which is due to the lack of clear structural transformations since independence. However, today the implementation of reform measures generates a number of negative reviews in the society related to the lack of awareness of citizens with the main vectors of change. In addition, the closure of hospitals leaves the population without proper medical care, while the general introduction of family medicine is met with caution as the special field “family medicine” is new and unpopular for Ukraine. Lack of sufficient knowledge about the basic principles of the functioning of family medicine and the absence of professional family doctors gives rise to further distrust of the people in the primary healthcare unit. Therefore, the medical reform instead of separating powers between all levels and areas of medical care and achieving global goals and results for the whole society and socio-economic development of the country is failing. In our study, we defined the concept of family medicine in its theoretical and practical application, proving that family medicine is the basis of the general well-being of society. And its development, modernization and popularization can become the first element in the general system of healthcare. An example of Central and Eastern European countries has shown that the phased introduction of family medicine is positively reflected in indicators of welfare and mortality rates, as well as on indicators of social and economic development of countries, etc. However, the lack of sufficient knowledge and the corresponding level of government interest in reforming the primary healthcare unit generates a zero effect from all actions taken. At the same time, non-professional family doctors invalidate the importance of the primary unit in the healthcare system. Within the framework of the study special attention was paid to the problems encountered by Ukraine on the way of implementation of medical reform. The basic components of such a problem, which originated in the absence of a clear and coordinated work of state authorities and local self-government was analyzed. Based on the foregoing, and on the experience of foreign countries, we have been offered ways to solve such problems and improve the general mechanism of primary healthcare.